The SLUGGS Survey: A New Mask Design to Reconstruct the Stellar Populations and Kinematics of Both Inner and Outer Galaxy Regions. (22nd August 2016) - Pastorello, Nicola; Forbes, Duncan A.; Poci, Adriano; Romanowsky, Aaron J.; McDermid, Richard; Alabi, Adebusola B.; Brodie, Jean P.; Cappellari, Michele; Pota, Vincenzo; Foster, Caroline
Abstract: Integral field unit spectrographs allow the 2D exploration of the kinematics and stellar populations of galaxies, although they are generally restricted to small fields-of-view. Using the large field-of-view of the DEIMOS multislit spectrograph on Keck and our Stellar Kinematics using Multiple Slits technique, we are able to extract sky-subtracted stellar light spectra to large galactocentric radii. Here, we present a new DEIMOS mask design named SuperSKiMS that explores large spatial scales without sacrificing high spatial sampling. We simulate a set of observations with such a mask design on the nearby galaxy NGC 1023, measuring stellar kinematics and metallicities out to where the galaxy surface brightness is orders of magnitude fainter than the sky. With this technique we also reproduce the results from literature integral field spectroscopy in the innermost galaxy regions. In particular, we use the simulated NGC 1023 kinematics to model its total mass distribution to large radii, obtaining comparable results with those from published integral field unit observation. Finally, from new spectra of NGC 1023, we obtain stellar 2D kinematics and metallicity distributions that show good agreement with integral field spectroscopy results in the overlapping regions. In particular, we do not find a significant offset between our Stellar Kinematics using Multiple Slits and the ATLAS 3D stellar velocity dispersion at the same spatial locations.